Vibration and Nonlinear Dynamic Analysis of Imperfect Thin Eccentrically Stiffened Functionally Graded Plates in Thermal Environments - Cong, Pham Hong; Duc, Nguyen Dinh (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: This paper presents an analytical approach to investigate the vibration and nonlinear dynamic response of imperfect thin eccentrically stiffened functionally graded material (FGM) plates in thermal environments using the classical plate theory, stress function and the Lekhnitsky smeared stiffeners technique. Material properties are assumed to be temperature-dependent, and two types of thermal condition are investigated: the uniform temperature rise; and the temperature gradient through the thickness. Numerical results for vibration and nonlinear dynamic response of the imperfect eccentrically stiffened FGM plates are obtained by the Runge-Kutta method. The results show the influences of geometrical parameters, material properties, imperfections, eccentric stiffeners, and temperature on the vibration and nonlinear dynamic response of FGM plates. The numerical results in this paper are compared with the results reported in other publications. Keywords: Vibration, nonlinear dynamic response, thin eccentrically stiffened FGM plates, classical plate theory, thermal environments.